2D Crystals in Three Dimensions: Electronic Decoupling of Single-Layered Platelets in Colloidal Nanoparticles - Kempt, Roman; Kuc, Agnieszka; Han, Jae Hyo; Cheon, Jinwoo; Heine, Thomas (Small, 2018)
2D crystals, single sheets of layered materials, often show distinct properties desired for optoelectronic applications, such as larger and direct band gaps, valley- and spin-orbit effects. Being atomically thin, the low amount of material is a bottleneck in photophysical and photochemical applications. Here, the formation of stacks of 2D crystals intercalated with small surfactant molecules is proposed. It is shown, using first principles calculations, that the very short surfactant methyl amine electronically decouples the layers. The indirect–direct band gap transition characteristic for Group 6 transition metal dichalcogenides is demonstrated experimentally by observing the emergence of a strong photoluminescence signal for ethoxide-intercalated WSe2 and MoSe2 multilayered nanoparticles with lateral size of about 10 nm and beyond. The proposed hybrid materials offer the highest possible density of the 2D crystals with electronic properties typical of monolayers. Variation of the surfactant's chemical potential allows fine-tuning of electronic properties and potentially elimination of trap states caused by defects.
CRIS-Team Scopus Importer:2022-04-14
Keywords: 2D materials; heterostructures; intercalates; optoelectronics; photoluminescence